Faith or Family? How Shincheonji Church of Jesus Members Navigate the Tragic Dilemma Between Religious Commitment and Filial Familism - Briggs, Mary (Nova religio, 2025)
In the first two decades of the twenty-first century, popular media and prominent Protestant figures alike have portrayed the Shincheonji Church of Jesus (hereon Shincheonji) as a destructive force on South Korean families, specifically alleging that it ruins the parent-child relationship. Based on the evidence of my qualitative interviews and written correspondences with a sample of Shincheonji members, I realized that members typically must contend with a seeming incompatibility between being faithful believers according to Shincheonji and good children according to traditional South Korean parenting. In this article, building on the work of Cheryl Mattingly, I argue that my participants and Shincheonji practitioners are faced with a tragic ethical dilemma following and feel torn between being faithful believers and being good children. To account for the tragic dimension of this dilemma, I first examine the importance of what I call South Korean filial familism. Second, I present a case study of one of my research participants, whom I refer to as Young-ja, to show the consequences of this tragic ethical dilemma.